2018
DOI: 10.1186/s40497-018-0090-x
|View full text |Cite
|
Sign up to set email alerts
|

Familial legacies: a study on Gujarati women and family entrepreneurship

Abstract: Among the states of India, the State of Gujarat in India presents numerous opportunities for entrepreneurship. This is the result of entrepreneurship ingrained in the culture and tradition of Gujarat. The significant aspect examined in this article is the link between family and women entrepreneurs in Gujarat. Evidences has been gathered from six cities of Gujarat covering Northern, Eastern, Southern, Western and Central zones to portray the overall picture of Gujarat. The findings from the evidence is to be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…The challenges women face due to gender stereotypes can be devastating. For example, Singh and Sebastian (2018) in their state-wide study of Gujarat, India found that women's main links to entrepreneurship are through the business occupations of their fathers and kinfolk. The process of their inclusion into the family enterprise is a matter of birth, not choice; and despite the exposure of these women to business practices, as women, they are not regarded as potential successors in business.…”
mentioning
confidence: 99%
“…The challenges women face due to gender stereotypes can be devastating. For example, Singh and Sebastian (2018) in their state-wide study of Gujarat, India found that women's main links to entrepreneurship are through the business occupations of their fathers and kinfolk. The process of their inclusion into the family enterprise is a matter of birth, not choice; and despite the exposure of these women to business practices, as women, they are not regarded as potential successors in business.…”
mentioning
confidence: 99%
“…The effects of birth order, sibling sex composition and family size on entrepreneurship is studied and indicate a mixed findings (Vladasel, 2019). Father's current or past profession influence women to become entrepreneurs (Singh and Sebastian, 2018;€ Ozsungur, 2019); whereas, men entrepreneurs choose a closely similar industry as their father's industry of employment (Hvide and Oyer, 2018). Perceived parental support has been found to influence entrepreneurial attribute, intention and action (Baluku et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women overcome cultural practices of mobility barrier when a male member accompanies them (Banihani, 2020). In some other traditional practices women are discouraged to work outside their homes and with strangers; thus, have to work in a family setting or build their own firms (Singh and Sebastian, 2018). However, a context of conflict and family-wellbeing lessens gendered roles and legitimizes women entrepreneurship (Althalathini et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is in the family sphere, where the values, habits, customs, lifestyle, and almost every aspect of our identity in adult life are developed. The impact of the family on different facets of the human being has been widely studied; such is the case of the entrepreneurial phenomenon (Aldrich & Cliff, 2003;Baron, 2002;López-Fernández et al, 2016;Santamaría et al, 2013;Singh & Sebastian, 2018). Since the beginning of studies on entrepreneurship, the relevant role of the family has been recognized (Aldrich & Cliff, 2003;Singh & Sebastian, 2018).…”
Section: Family-business Balance: a Gender Perspectivementioning
confidence: 99%